Sucralfate and Honey in Burn Wound Healing: An Article Review - Wardhana, Aditya; Farhana, Nadya (The Lingkar Studi Bedah Plastik Foundation and is affiliated with the Department of Plastic Surgery, Faculty of Medicine, Universitas Indonesia., 2024)
Introduction : Several studies stated that sucralfate and honey topically promote wound healing process. Sucralfate has been used for stomatitis, excoriation in perianal and peristomal, ulcers, and burn wounds. Honey as a food which is taken orally, is also used topically for several kind of wounds including burn wounds. However, there is no study reviewing sucralfate and honey in burn wounds.Method : Literature review was conducted from 1st until 6th of June 2022 using the terms of “honey”, “sucralfate”, “burns” and “wound healing”. Pubmed, Cohrane, Science Direct, Scopus, and Google Scholar were the online data bases we used. We identified eight studies, three trials evaluated the effects of sucralfate in burn wounds and five trials evaluated the effects of honey in burn wounds.Result : 3 Randomized Controlled Trials (RTCs) (n=170) about the effects of sucralfate and 5 RCTs (n=474) reported the effects of honey in burn wounds. Both Sucralfate and Honey group had similar wound healing duration around 18 days and had early sign of wound healing by day 7. Honey has faster complete wound healing compared to sucralfate by day 21. Honey has remarkable antimicrobial effect within one hour. No side effects were reported in both trials. Both honey and sucralfate reduce the necessity for skin grafting.Conclusion: Both sucralfate and honey have similar rapid re-epithelization in burn wounds, but honey has faster complete wound healing by day 21. Both has similar antimicrobial effect, no side effects, and reduce the necessity for skin grafting.